Effects of Heating and Liquid Nitrogen on Mechanical Characteristics and Rockburst Characteristics of Granite - Xue Li; Yi Xue; Fa-ning Dang; Zhihao Zhang; Lin Zhu; Shanjie Su; Shengcheng Wang; Ruifu Liu (Geofluids)
Due to the depletion of shallow resources and the reduction of the space for human life and development, in recent years, human beings began to gradually expand to the deep underground. The increase of development depth will bring a series of safety problems, so it is particularly important to study and deal with rockburst. In this paper, based on laboratory tests, relevant literature, and research at home and abroad, the TAWD-2000 electrohydraulic servo rock mechanics testing machine and PIC-2 acoustic emission (AE) testing system are used. Uniaxial compression tests and AE monitoring tests were carried out on granite samples to analyze the property and AE characteristic parameters of granite under the action of liquid nitrogen (LN2) and to further study the fracture mode of granite. The following conclusions can be obtained: the LN2 cooling has a deterioration influence on the strength of rock, and the elastic modulus and peak stress of granite show a downward trend with the increasing number of cycles. With the cycle times of LN2 actions increasing, the AE ring count of granite and the frequency and amplitude of energy in each stage have an upward trend. When the rock reaches the failure stage, the energy at the catastrophe point increases, and the ring count also increases sharply. The RA-AF diagram of AE parameters can characterize two failure modes of rock, tensile failure and shear failure. In the process of fracture of granite samples, shear cracks dominate, leading to shear failure or compression failure of granite. Based on the method of elastic energy, the tendency index of rockburst of granite samples under different working conditions is calculated. The tendency of rockburst decreases with the decrease of elastic modulus. Under the repeated action of LN2, the tendency of rockburst of granite samples presents a downward trend, and the action of LN2 reduces the probability of rockburst to a certain extent.